2015
DOI: 10.1252/jcej.14we358
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanism of True 2D Granular Flows

Abstract: Most previous experimental investigations of two-dimensional (2D) granular column collapses have been conducted using three-dimensional (3D) granular materials in narrow horizontal channels (i.e., quasi-2D condition). Our recent research on 2D granular column collapses by using 2D granular materials (i.e., aluminum rods) has revealed results that differ markedly from those reported in the literature. We assume a 2D column with an initial height of h0 and initial width of d0, a defined as their ratio (a =h0/d0)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…Nguyen et al [9] showed that there are differences between his results with those of previous authors.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…Nguyen et al [9] showed that there are differences between his results with those of previous authors.…”
Section: Introductionmentioning
confidence: 58%
“…A series of physical experiment model (in the laboratory), barrier is used to keep stable granular column during the experimental model setup stage. Barrier will be removed appropriately [9] to minimize the influence on granular columns collapse process. The numerical experiments which don't have barrier, the initial setup for the granular column with initial column height h 0 and initial granular column width d 0 in Figure 1.…”
Section: Setup For Model Of Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We simulate the experiment of Nguyen [2015] by using different viscous value to test the influence of viscosity. From Fig.…”
Section: Effect Of Viscositymentioning
confidence: 99%